D. M. Ovsianyko-Kulikovsky as an Orthologist: the Cognitive-evolutionary Coverage - Popov, Sergiy (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The article is devoted to the cognitive-evolutionary coverage of D. M. Ovsianyko-Kulikovsky's beliefs as an orthologist who expressed his orthological convictions regarding the norms of syntactic agreement of adjectives with homogeneous noun phrases. The scholar categorically denied the possibility of such agreement in the plural, despite the fact that in the eighteenth century such agreement was already quite common in usage as a logical agreement of the plural adjective with more than one noun.The article proves that, defending the illogical agreement of such adjectives in the singular, the scientist demonstrates a superficial perception of such agreement as necessary only with regard to one, closest postpositive noun in the syntagm. The main provisions of the cognitive-evolutionary theory of language are revealed, the essence of which involves the algorithm "perception → logic of thinking → logic of language" and one of the central concepts of which is the concept of superficiality of perception as an orientation to the closest, most noticeable features of phenomena, the categorization of which is often erroneous.Attention is drawn to the fact that the scientist's arguments against the possibility of the considered plural agreement are characterized by emotionality, unscientific nature and disregard for the opposite beliefs of both journalists of his time and famous linguists - both his predecessors and contemporaries ‒ unjustified for the scientific style. It is emphasized that such a position of D. M. Ovsianyko-Kulikovsky is an argument to taste, i.e. one of the two weakest arguments in the theory of argumentation, which in linguistics can be used only to characterize stylistic phenomena, which the agreement under consideration is not.The article concludes that, denying the possibility of such agreement, D. M. Ovsyanyko-Kulikovsky was a very conservative orthologist who, guided by superficial perception, neglected the linguistic facts of usage, journalists and other linguists. Since he had and still has his followers, whose books are still being reprinted, we can speak of the existence of an anti-language-evolutionary conservative party in Russian-language orthology, which can be recognized as quite natural for Russian society as a whole.